Analisis Semantik Makna Kata /Nashara/ نصر dan Derivasinya dalam Al-Qur’an / Semantic Analysis of the Meaning of the Word "نصر" and Its Derivation in the Qur'an - Khoiriyatunnisa, Luthfia; Asfar, Dedy Ari; Syahrani, Agus (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The Quran is a blessing sent down by Allah to the prophet Muhammad through the Arabic language. In the Quran is found a word that represent a lot of meaning, which is called musytarak lafzi (polysemy). For example is the word nashara and its derivations. The corpus data used in this research is the Quran and the translation, while the collecting of this data is using a digital based corpus that is the Quran Arabic Corpus (https://corpus.quran.com/). This study aims to analyse morphological aspect and semantics side of /nasاara/, since it generates many kind of word as it's derivation; and in the same time those derivation words have various meaning, relying on the context and lexical sense. In this research, the writer uses the semantic lexical analysis approach because this research is to analyse a word. This research is classified as a qualitative research with descriptive-analytic method. The findings of the research regarding the word nashara and its derivations show a few things, such as; 1) The use of the word nashara and its derivations in the Quran in ayat and surah is in the form of fi'il mudhari, fi'il amr, masdar, ism fa'il, ism maf'ul, and shighat mubalaghah, 2) The meaning of the word nashara and its derivations are lexical and contextual. The lexical meaning is to help and the derivations are referred to the innitial meaning. In the Quran, the word nashara and its derivations is used a lot to show several meaning, such as; winning, avenge, massacre, and christian. مستلخص في القرآن هناك كلمة واحدة تشير إلى معاني كثيرة، ويسميىت بالمشترك اللفظي، مثلا لفظ "نصر" ومشتقاته. يهدف هذا البحث لمعرفة الصيغ الصرفية للفظ "نصر" ومشتقاته في القرآن الكريم ومعرفة المعاني المتضمنة في لفظ "نصر" ومشتقاته في القرآن الكريم. في هذ البحث، المدخل المستخدم هذا البحث هو نهج التحليل الدلالي المعجمي لأن البحث حلل اللفظ. يصنف هذا البحث كبحث نوعي مع أساليب وصفية تحليلية. مصدر هذه البيانات البحثية هو نص القرآن الكريم و ترجمتها، و أما أثناء جمع البيانات باستخدام موقع القرآن العربي (corpus.quran.com). وصل نتائج البحث في اللفظ "نصر" و مشتقاقه يظهر عدة أشياء، وهي : ١) إن في القرآن الكريم استعمال لفظ " نصر" ومشتقاته في مختلف الآيات والسور بالبنية الصرفية توزع بين فعل ماض ومضارع وأمر ومصدر واسم فاعل واسم مفعول وصيغة المبالغة. (٢) إن لفظ "نصر" ومشتقاته له المعاني المعجمية والسياقية. من المعاني المعجمية؛ المساعدة. استعمال لفظ "نصر" في القرآن على نطاق واسع للدلالة على عدة معاني، مثل، الفتح، الفوز، التّذرّع، الحزب، و النصراني. الكلمات المفتاحية : معنى؛ لفظ "نصر"؛ الدلالة؛ الإشتقاق